BRICS and Climate Change Law: An Opportunity to Save the Planet - Maksim Lavrik; Amos Saurombe (Potchefstroom Electronic Law Journal)
Climate change is a global problem requiring the cooperation of different states to cope with it. This global challenge has been a major concern for the international community mainly through several United Nations Treaties and other international bodies. Despite having a huge appeal to all countries of the world, the implementation of climate change interventions has yet to produce the desired results. The BRICS Plus initiative presents an opportunity for further cooperation with like-minded countries that are at the forefront of driving the global economy. BRICS Plus also presents an opportunity for cooperation to tackle climate change. This paper analyses how countries' cooperation under the BRICS contributes to developing the international climate change regime. BRICS is a bloc of top emerging economies - Brazil, Russia, India, China, and South Africa - which has been enlarging since January 2024 by adding new member states such as Egypt, Ethiopia, Iran, Saudi Arabia, and the United Arab Emirates (UAE). This paper evaluates relevant provisions of the Johannesburg II Declaration of 2023 and the climate pledges of original and new BRICS members expressed in their Nationally Determined Contributions (NDCs) under the Paris Agreement. Based on this evaluation, the article concludes with a common vision of the development of climate change policy by the bloc and how differences and similarities of approaches of the BRICS members contribute to the cooperation for addressing the climate change challenge.